Antagonistic activity of Wickerhamomyces anomalus, Kluyveromyces marxianus and Lactobacillus paracasei against growth and aflatoxin production of Aspergillus flavus in corn silage - Rungchaiwattanakul, Tassaporn; Chareonpornwattana, Supat; Sirisomboon, Cheewanun Dachoupakan (Agriculture and Natural Resources, 2022)
Importance of the work: The contamination of Aspergillus section Flavi producing aflatoxins during ensiling is a main problem resulting in corn silage spoilage. Objectives: To evaluate the antagonistic activities of yeasts and a lactic acid bacterium against A. flavus. Materials & Methods: Individual yeast culture, mixed yeast culture (Wickerhamomyces anomalus MSCU 0652 and Kluyveromyces marxianus MSCU 0655) and Lactobacillus paracasei AN3 were tested for their antifungal activities against A. flavus growth and its aflatoxin production both in vitro and in corn silage. Results: In vitro studies showed inhibitory activities of Lactobacillus paracasei and mixed yeasts against aflatoxin production but lower activity against fungal growth. The co-cultures of L. paracasei and mixed yeasts were used as starter for sterile and non-sterile corn ensiling. For the sterile condition, a substantial reduction of pH was observed 1 day after ensiling. The growth of mixed yeasts and L. paracasei was not mutually affected, but that of A. flavus was completely inhibited in 7 d with the reduction of aflatoxin production after 14 d of ensiling. For corn silage, mixed yeasts and L. paracasei at a ratio of 1 × 106:1 × 108 colony forming units/g inhibited fungal growth and reduced aflatoxin production at 5 d and 7 d of ensiling, respectively, with no effect on nutritional values. Main finding: The mixed culture of selected yeasts and a lactic acid bacterium showed potential for use as a biocontrol agent in silage to improve silage quality.